2020
DOI: 10.1016/j.ijfatigue.2020.105676
|View full text |Cite
|
Sign up to set email alerts
|

Damage and fatigue life prediction of short fiber reinforced composites submitted to variable temperature loading: Application to Sheet Molding Compound composites

Abstract: The majority of fatigue life prediction models which have been proposed for the Short Fiber Reinforced Composite (SFRC) materials have been developed for constant temperature. However, in real situations, SFRC structures are subjected to variable temperature. This study focus on the response of SFRC composites subjected to different sequences (or blocks) under variable temperature conditions. Experientially, this kind of study requires a lot of investment from the point of view of cost and time. In this paper,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Once validated, the approach is used to highlight the effect of types and order of the cyclic sequences. Note that a recent paper [20], the efficiency of the proposed method has also been demonstrated in the case of variable temperature. Therefore, a general algorithm involving both variable amplitude and temperature is proposed.…”
Section: T-b B-tmentioning
confidence: 83%
See 2 more Smart Citations
“…Once validated, the approach is used to highlight the effect of types and order of the cyclic sequences. Note that a recent paper [20], the efficiency of the proposed method has also been demonstrated in the case of variable temperature. Therefore, a general algorithm involving both variable amplitude and temperature is proposed.…”
Section: T-b B-tmentioning
confidence: 83%
“…Three tests were carried out for each type of microstructure and type of sequence in order to demonstrate the reproducibility of the experimental results. Because of the high scattering microstructure well known in SMC composites, the microstructure of each specimen was firstly selected on the basis of ultrasonic measurements described in [19,20].…”
Section: Results and Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been conducted concerning the mechanical behaviour of several SMC composites formulations [13,[21][22][23][24][25]. The focus has been on the multi-scale experimental analysis and modelling of the mechanical behaviour and damage of this class of composites materials [27,28]. It has been demonstrated that the non-linear behaviour of a standard SMC (such as the one in study) is mainly governed by fibre-matrix interface failure [21][22][23].…”
Section: Previous Workmentioning
confidence: 99%
“…Jain et al presented a stress-number of cycles (S-N) curve that considered the effect of the stiffness drop according to the fiber orientation distribution during a fatigue test [19]. Tamboura et al investigated the damage and fatigue life prediction of short-fiber-reinforced composites [20]. Therefore, even in recent studies, fatigue life prediction by applying the degradation of the elastic modulus according to the stiffness reduction and damage of the composites were being made.…”
Section: Introductionmentioning
confidence: 99%